Моделювання лазерно-індукованих інтерференційних структур - Березюк, Геннадій; Трохимчук, Петро; Berezyuk, Hennadiy; Trokhimchuck, Petro (Східноєвропейський національний університет імені Лесі Українки, 2013)
Наведено результати моделювання процесів утворення лазерно-індукованих інтерференційних структур із використанням плазмон–поляритонної моделі, моделі Фейгенбаума, теорії каскадних процесів, застосовної до хімічних зв’язків. Отримане задовільне узгодження експериментальних результатів та теоретичних оцінок.; Results of modeling of processes the creation laser induced interference structures with help of polariton- plasmon model, theory of cascade processes for chemical bond are discussed and analyzed. An influence of parameters of laser irradiation (time, spectrum and polarization of irradiation) on formation of interference structures is discussed. It is shown that the plasmon polariton and cascade models complement each other. It is suggested that due to the fact that the Feygenbaum model allows to describe only doubling the interference patterns should develop methods of fractal dynamics. Normally agreement of experimental and theoretical data is received.
Modeling of Laser-induced Interference Structures
Keywords: релаксаційна оптика; інтерференція; наноструктури; плазмон-поляритонна модель; модель Фейгенбаума; каскадна модель; Relaxed Optics; interference; nanostructures; plasmon-polariton model; Feygenbaum model; cascade model